Temperature controlled properties of sub-micron thin SnS films. (25th April 2018) - Nwankwo, Stephen N; Campbell, Stephen; Reddy, Ramakrishna K T; Beattie, Neil S; Barrioz, Vincent; Zoppi, Guillaume
Abstract: Tin sulphide (SnS) thin films deposited by thermal evaporation on glass substrates are studied for different substrate temperatures. The increase in substrate temperature results in the increase of the crystallite size and change in orientation of the films. The crystal structure of the films is that of SnS only and for temperatures ≤300 °C the films are of random orientation, whereas for higher temperatures the films become (040) oriented. The variation of Sn/S composition was accompanied by a reduction in optical energy bandgap from 1.47 to 1.31 eV as the substrate temperature increases. The Urbach energy was found stable at 0.169 ± 0.002 eV for temperature up to 350 °C. Photoluminescence emission was observed only for films exhibiting stoichiometric properties and shows that a precise control of the film composition is critical to fabricate devices while an increase in grain size will be essential to achieve high efficiency.